Proyecto de restauración y adecuación de uso actual del palacio de Huitziméngari en Pátzcuaro Michoacán - Perdomo Pantoja, Carmen Lucia; Tello Calderón, Gonzalo (Universidad Michoacana de San Nicolas de Hidalgo, 2016)
The heritage value of a building, defined by its historical and cultural value, makes it an object of study and protection; but the process of restoring and preserving a historical building, entails the satisfaction of the deepest human needs, such as the recognition of being, by the objects of the past and the search for memory and identity conservation, individually and collectively. The present work describes a project of restoration and adequacy of current use of the property named as "The Palace of Huitziméngari". which originally belonged to Don Antonio Huitziméngari, son of the last emperor of the Purépecha empire, placing the building at an early stage in the sixteenth century. The building now has various damages, caused by different agents, causing a general affectation, it needs intervention in order to stop the deterioration and preserve this important building, which has witnessed the historical evolution of the región, in addition to its high architectural value, it is symbol of identity for the Purépecha community. The document essentially presents an integral and multidisciplinary project that covers the theoretical and technical foundations; and the implementation of methodologies, principles, guidelines and recommendations that involve and regulate the treatment of historical monuments, and projects of this kind. The exposed content implies the development of studies and site surveys required to determine the current situation of the building, as well as the basis of the intervention criteria, which resulted in the restoration and integration projects with the implementation of new spaces aimed to expand productivity and profitability of the property, in order to ensure its safekeeping against the requirements of the activities of its current use and the community occupying it.

El valor patrimonial de una construcción, definido por su valor histórico-cultural, lo convierte en objeto de estudio y protección; mas el proceso de restaurar y conservar una edificación histórica conlleva la satisfacción de las necesidades más profundas, propias del ser humano, como lo es el reconocimiento del ser, a través de los objetos del pasado y la búsqueda de la conservación de la memoria y la identidad, individual y colectiva. El presente trabajo expone el proyecto de restauración y adecuación de uso actual del inmueble conocido como "El Palacio de Huitziméngari", que perteneciera en su origen a Don Antonio Huitziméngari, hijo del último emperador del imperio purépecha, situando a la construcción en una primera etapa en el siglo XVI. El edificio presenta actualmente diversos daños, causados por diferentes agentes, que provocan una afectación general, siendo la finalidad de una intervención frenar el deterioro y conservar esta relevante edificación, que ha sido testigo del devenir histórico de la región y que además de su alto valor arquitectónico, es un símbolo de identidad para la comunidad purépecha. El documento esencialmente plantea un proyecto integral y multidisciplinario que abarca los fundamentos teóricos y técnicos; así como la implementación de las metodologías, postulados, lineamientos y recomendaciones que involucran y regulan el tratamiento de los monumentos históricos y los proyectos de esta índole. El contenido expuesto conlleva el desarrollo de los estudios y levantamientos necesarios para determinar el estado actual del inmueble, así como la fundamentación de un criterio de intervención, que derivó en el proyecto de restauración y de integración de nuevos espacios que buscan ampliar la productividad y rentabilidad del inmueble, con el objeto de garantizar su salvaguarda ante los requerimientos de las actividades de su uso actual y de la comunidad que lo ocupa.
Facultad de Arquitectura. Especialidad en Restauración de Sitios y Monumentos
Keywords: http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/3206; info:eu-repo/classification/cti/4; FA-E-2016-0052; Cultura; Identidad purépecha|Actualidad